The effectiveness of vision screening by school nurses in secondary school. Issue 1 (January 1994) - Jewell, G; Reeves, B; Saffin, K; Crofts, B
Abstract : Vision screening of 13 and 15 year old children by school nurses in Oxfordshire has declined in recent years due to the pressure of other commitments. A study was carried out to evaluate the likely consequences of failing to provide vision screening for secondary schoolchildren, in order to make a decision about the future of the service. Parents were also asked to complete a questionnaire about their children's past eye histories. Eight schools that had had no vision screening for at least three years participated in the study. Overall, 3.8% of children between 13 and 15 years old had a visual acuity of worse than 6/12 in one or both eyes, that is they failed vision screening; there was no evidence that this percentage increased significantly across this age range. Less than 1% of children were prescribed and wore spectacles as a consequence of failing vision screening and no new cases of eye pathology were detected. Questionnaire responses suggested that about 50% of children who did not wear spectacles had had an eye examination in the previous two years. The results indicate that vision screening is not the best way to meet the eye/vision needs of secondary schoolchildren. Strategies for targeting the school nursing resource more appropriately are being considered.